Potential blockchain applications in waqf for sustainability: a Middle East and Asia perspective - Balkis Kasmon; Siti Sara Ibrahim; Sharfizie Mohd Sharip; Asmak Ab Rahman; Nurul Fadly Habidin (Penerbit Universiti Kebangsaan Malaysia, 2023)
Waqf development in Malaysia benefits the economy and society, mostly in terms of facilities, education, investment, and others. Due to the massive development of the waqf industry, digitalization is deemed as a facilitative instrument in the operation of waqf. With the usage of digital platforms, the collection of waqf funds becomes more efficient and widely dispersed among Muslims. In this context, blockchain has become a new phenomenon, functioning as a ground-breaking innovation connected to bitcoin. The core idea behind a blockchain is that its users can access the ledger independently of a third party. Additionally, the blockchain counts all network nodes equally, taking human and computer communication into account without any special treatment or discrimination. Without realizing it, several waqf institutions have already applied this approach using their own platform. Therefore, this study aims to systematically review the potential application of blockchain in waqf institutions by referring to previous applications in other countries in the Middle East and Asia such as Oman, Bahrain, United Arab Emirates, Singapore, Indonesia, and Malaysia. Methodology wise, this paper employs the Systematic Literature Review which consists of the processes of identification in evaluation of the data from September 2022 until October 2022 by using related keywords to study. Secondly, is screening process which entails the process of choosing articles based on inclusion and exclusion criteria. This study screened all the 49 selected articles by choosing the criteria for articles selection which is done automatically based on the sorting function available in the database. Thirdly, eligibility which the authors manually monitored the retrieved articles to ensure all the remaining articles (after the screening process) are in line with the criteria. Lastly, the quality appraisal which to ensure that the substance of the articles was of high quality. The findings are important for waqf institutions to realize the potential benefit of blockchain in improving the efficiency of waqf operations towards attaining sustainable socio-economic development.